Controlled levitation of bulk superconductors. - Nagashima, K.
Levitation of bulk Y-Ba-Cu-O superconductors could successfully be controlled using a Bi-Sr-Ca-Cu-O superconducting electromagnet. It was found that stable levitation without tilting was obtained only when the sample trapped a certain amount of field, the minimum of which depended on the external field and the sample dimensions. We also employed a novel analysis method for levitation based on the total energy balance, which is much simpler than the force method and could be applied to the understanding of general levitation behavior. Numerical analyzes thus developed suggested that stable levitation of superconductors with large dimensions can only be achieved when the induced currents can flow with three dimensional freedom
Keywords: Bi-Sr-Ca-Cu-O.; Y-Ba-Cu-O.; Bulk superconductors; Induced currents; Levitation; Total energy balance